The wish - Sparks, Nicholas (Grand Central Publishing, 2021)
1996 was the year that changed everything for Maggie Dawes. Sent away at sixteen to live with an aunt she barely knew in Ocracoke, a remote village on North Carolina's Outer Banks, she could think only of the friends and family she left behind . . . until she met Bryce Trickett, one of the few teenagers on the island. Handsome, genuine, and newly admitted to West Point, Bryce showed her how much there was to love about the wind-swept beach town-and introduced her to photography, a passion that would define the rest of her life.